Secondary prevention of HIV infection: the current state of prevention for positives. - Fisher, Jeffrey D; Smith, Laramie (Current opinion in HIV and AIDS, 2009)
To provide a state-of-the-science review of the literature on secondary prevention of HIV infection or 'prevention for positives' (PfP) interventions.
Keywords: Animals; Female; HIV Infections; Humans; Intervention Studies; Male; Risk-Taking; Secondary Prevention